ANALISIS PRODUKSI SERASAH MANGROVE DI DESA RUYUNG KECAMATAN MASJID RAYA, KABUPATEN ACEH BESAR - Harum Farahisah; Agung Prasetiawan; Khairunnisa Khairunnisa; Chitra Octavina (Jurnal Kemaritiman: Indonesian Journal of Maritime, 2023)
Mangrove litter is a supplier of organic matter and can increase the fertility of mangrove ecosystems. This study aims to analyze the production of mangrove litter, as well as the density and physico-chemical parameters of the mangrove ecosystem in Ruyung Village, Great Mosque District, Aceh Besar District. This research was conducted in March-April 2023. There are 3 data collection stations. Litter collection was carried out using a 1x1 m2 litter trap which was taken every 7 days in 1 month. The total production of mangrove litter at the research location was 119.30 gbk/m2/30 days. The density of mangroves at the study site is included in the criteria for dense mangroves. The physical and chemical parameters of the waters also support mangrove life.